(untitled) (Applied Biological Research, 2015)
A field experiment was carried out at BCKVV, West Bengal (India) during kharif 2011 and 2012 to assess the performance of 6 rice varieties under conventional and SRI methods of cultivation with respect to growth, yield and quality parameters. The results revealed that the method of crop production significantly affected plant height and root length, whereas varieties exerted significant impact on dry matter accumulation, LAI, root length and root dry weight. The SRI method produced 58.6 and 21.8% higher grain and straw yields, respectively, than conventional system. The rice quality was unaffected by change in cultivation method. Rice variety ‘Dehrdun’ gave better response with respect to kernel length and L:B ratio than other varieties under SRI method.. The physico-chemical properties of soil after harvest was appreciable improved. Among the different varieties ‘Badsha bhog’ gave higher gross return, net return and B: C ratio under SRI method.